2023
DOI: 10.1002/jor.25642
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periprosthetic bone loss on the failure risk of tibial total knee arthroplasty

Abstract: The effect of long‐term periprosthetic bone loss on the process of aseptic loosening of tibial total knee arthroplasty (TKA) is subject to debate. Contradicting studies can be found in literature, reporting either bone resorption or bone formation before failure of the tibial tray. The aim of the current study was to investigate the effects of bone resorption on failure of tibial TKA, by simulating clinical postoperative bone density changes in finite element analysis (FEA) models and FEA models were created o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…Albright et al described an association between previous fragility fracture and increased susceptibility to infection after total knee arthroplasty (TKA) 26 , as bones with low density or compromised integrity possess reduced resistance to bacteria, rendering them more vulnerable to infection. Soltanihafshejani et al results showed poor bone health contributes to an increased risk of implant failure 26,27 . Implants rely on strong, healthy bone to provide optimal stability and support.…”
Section: Surgical Risks Associated With Poor Bone Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Albright et al described an association between previous fragility fracture and increased susceptibility to infection after total knee arthroplasty (TKA) 26 , as bones with low density or compromised integrity possess reduced resistance to bacteria, rendering them more vulnerable to infection. Soltanihafshejani et al results showed poor bone health contributes to an increased risk of implant failure 26,27 . Implants rely on strong, healthy bone to provide optimal stability and support.…”
Section: Surgical Risks Associated With Poor Bone Healthmentioning
confidence: 99%
“…Risk factors include older age and female sex, hence the recommendation to start screening women at a younger age than men, low BMI [50][51][52][53][54] with low BMI defined as ,21 55 , a history of previous fracture, and a family history of osteoporosis 46,47 . A list of medications and medical conditions leading to increased risk of poor bone health, along with the adverse orthopaedic surgical outcomes associated with poor bone health, are outlined in Table II 2,9,[26][27][28][29][30][31][50][51][52][53][56][57][58][59][60][61][62][63][64][65][66][67] .…”
Section: Screening Diagnosis and Risk Factors For Poor Bone Healthmentioning
confidence: 99%
See 2 more Smart Citations